Fabrication of flower clusters‐like superhydrophobic surface via a UV curable coating of ODA and V‐PDMS. Issue 46 (4th July 2019) - Shen, Lixiang; Lai, Yingying; Fu, Heqing
ABSTRACT: In this work, a flower clusters‐like superhydrophobic surface was fabricated via an ultraviolet (UV) curable coating of octadecylamine (ODA) and vinyl‐terminated polydimethylsiloxane (V‐PDMS). ODA self‐assembled into many flower clusters‐like structures on the surface of the coating, increasing the roughness of the coating surface without additional nanoparticles. V‐PDMS formed a highly crosslinked network under a UV lamp, which would be helpful for a robust superhydrophobic surface. The obtained PDMS/ODA fabric showed water contact angle of 161° and sliding angle of 5°. The durability of the superhydrophobic surface was tested by water impacting, tube brush scrubbing, knife scratching, hand twisting, finger pressing, tape adhesion, abrasion, continuous rinsing, and chemical conditions. The experimental results indicated that the superhydrophobic surface have good durability for long service life. Moreover, the PDMS/ODA fabric could selectively absorb oils from water with good separation performance. This work will provide a facile, low cost, and versatile method to prepare superhydrophobic surfaces, and enhance their efficiency of oil–water separation. © 2019 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2019, 136, 48210. Abstract : A flower clusters‐like super hydrophobic surface.